Space Technology for Agricultural Development - Sai, M. V. R. Sesha (International Journal of Economic Plants, 2016)
The twin challenge of faster and more-inclusive agricultural growth of our country calls for concerted efforts towards natural resources management and disaster management. Rapid developments occurring in the cutting edge technologies such as agricultural biotechnology and information and communication technology together with contemporary modeling techniques enable developing an appropriate framework for implementation at the grass-root level. In India, the space programme has been conceived to meet the national imperatives and the societal needs. Space technology, with its three major components viz., the satellite communications, the close weather watch and the Earth observations, plays a significant role towards national development. Agriculture has a strong reliance on the natural resources. In this regard, Earth Observation satellite data have been extensively used in India towards building up the national natural resource database with an objective to improve the resource use efficiency for the overall development of the country. Remote sensing has enabled mapping, assessing, monitoring and management of various natural resources like soil or land, forestry, geology, water, ocean and atmosphere, etc. It has further enabled monitoring of environment and thereby helping in planning for their sustained and enhanced use. In the last four decades it has become a major tool for collecting information on several aspects of natural resources available on the Earth. With the availability of remotely sensed satellite data of varying specifications, the applications of this technology have multiplied both for civilian and strategic purposes.